Subjective expectations of survival and economic behaviour - Cormac O'Dea; David Sturrock (Institute for Fiscal Studies (IFS), 2018)
This paper investigates individuals' expectations about their own survival to older ages and compares patterns in average responses about survival chances with actual and projected survival rates. The extent to which individuals have, on average, accurate expectations about survival to older ages is important in a context of increasing personal responsibility for and control over the accumulation and use of savings for retirement.
Keywords: D14; D84; D91; J14; 330; Survival expectations; savings; wealth accumulation; annuitisation